Formação e Evolução da Indústria do estanho no Brasil. - Cuter, Julio Cesar (2005)
This paper analyzes the evolution of tin industry in the Brazilian Economy, verifying the basis of its origin and development, and assuming as a starting point the characteristics of a worldwide oligopoly. The history of national tin industry is analyzed from its initial stages, going through the development of the 1980-1990 decade, with all the consequences for the international market. The changes in the Brazilian Economy and Industry that took part during the 90 s are emphasized, showing how they led to the current scenario. Other than that, this work points out the importance of the Amazon occupation and exploration model in the process of the industry development, thus the government role in the sector. It also analyzes the insertion of national production in the international market and its consequences, such as the collapse of the so far existing cartel.